Culturing marine bacteria from the genus Pseudoalteromonas on a cotton scaffold alters secondary metabolite production. Issue 5 (1st October 2018) - Timmermans, Marshall L.; Picott, Katherine J.; Ucciferri, Lorena; Ross, Avena C.
Abstract: The discovery of secondary metabolites from marine microorganisms is beset by numerous challenges including difficulties cultivating and subsequently eliciting expression of biosynthetic genes from marine microbes in the laboratory. In this paper, we describe a method of culturing three species from the marine bacterial genus Pseudoalteromonas using cotton scaffold supplemented liquid media. This simple cultivation method was designed to mimic the natural behavior of some members of the genus wherein they form epibiotic/symbiotic associations with higher organisms such as sponges and corals or attach to solid structures as a biofilm. Our scaffolded cultivation is highly effective at stimulating an attachment/biofilm phenotype and causes large changes to metabolite profiles for the microbes investigated. Metabolite changes include alteration to the production levels of known molecules such as violacein, thiomarinol A, and the alterochromide and prodiginine families of molecules. Finally and critically, our technique stimulates the production of unknown compounds that will serve as leads for future natural product discovery. These results suggest our cultivation approach could potentially be used as a general strategy for the activation of silent gene clusters in marine microbes to facilitate access to their full natural product biosynthetic capacity. Abstract : We describe a method for culturing the marine bacterial genus Pseudoalteromonas using cotton scaffold supplemented liquid media. Our technique is highly effective at stimulating an attachment/biofilm phenotype and simultaneously causes considerable changes to metabolite profiles for the microbes investigated.